Pre-Service Teachers’ Perception toward Teaching Skills Development: Experience in Teaching-Campus Program - Maharani, Mega Mulianing; Arsiska, Noca Verona; Widiyati, Elok (Universitas Islam Sultan Agung, 2025)
Even though pre-service teachers are crucial to raising educational standards, there is a disconnect between classroom theory and real-world practice. Preservice teachers' perspectives on the Teaching-Campus Program's impact on their professional growth as educators are the focus of this research. The research team used quantitative methods and descriptive analysis to gather data from a closed-ended questionnaire. The questionnaire assessed eight different areas of teaching abilities: lesson planning, explanation, variation, questioning, reinforcement, classroom management, small group instruction, and small group discussion facilitation. With a mean score of 90.63 percent, the results demonstrated that the pre-service teachers' capacity to articulate ideas clearly and provide appropriate examples was the strongest competency. Questioning skills followed with a mean score of 90.00%, while opening and closing the lessons skills scored 89.69%. Reinforcement skills recorded a mean score of 88.33%, and classroom management skills reached 87.71%. Small group teaching skills and variation skills achieved mean scores of 85.32% and 85.00%, respectively. Guiding small group discussions skills obtained the lowest score of 80.94%, indicating the need for further improvement in this area. As a whole, the Teaching-Campus Program has helped prepare future educators for the classroom by connecting classroom practice with classroom theory. If they want to advance in their careers, they should get more training on how to lead group discussions and how to change up their teaching methods.